Cost-effective, low density, carbon soot doped resorcinol formaldehyde composite for ablative applications - Badhe Y.; Balasubramanian K.; Gupta R. (My University, 2025)
Successful in situ polymerization of highly ablation-resistant composites of resorcinol formaldehyde (RF) modified with carbon soot (CS) was carried out for the first time. The composites exhibited a comparatively high char yield, up to 59.7% at 800 °C, and while undergoing ablation by an oxyacetylene flame displayed exceptionally low linear and mass ablation rates of 0.019 mm s-1 and 0.053 g s-1, respectively. Microstructure analysis of a surface ablated for 60 s revealed a uniform pattern of closely knit carbon nanobead-like structure which ensured enhanced ablation resistance. The formation of turbostratic carbon guaranteed a significantly improved thermal insulation property of the ablative composite at a higher temperature. An XRD graph showed peaks at 24° and 44°, corresponding to carbon nanobeads and insulating turbostratic carbon. The ability of RF to replace conventional phenol formaldehyde (PF) resin was confirmed. A CS/RF ablative composite during ablation also displayed reduced erosive losses and hence can be potentially used as a backbone material of a thermal protection system required for ablative applications. This journal is © The Royal Society of Chemistry 2015.